Screening Of Pulmonary Hypertension in Methamphetamine Abusers (SOPHMA): rationale and design of a multicentre, cross-sectional study - Duo Huang; Pak Hei Chan; Yangyang Cheng; Chi-Kwong Tung; Albert Kar Kin Chung; Wan-Wan Liu; Ming Lam; Wai-Chi Chan; Chung-Wah Siu; Jo Jo Hai (BMJ Open)
Introduction Methamphetamine misuse is classified as a ‘likely’ risk factor for pulmonary arterial hypertension (PAH). Nevertheless, the actual prevalence of and a screening strategy for PAH in methamphetamine users have not been established. We plan to study the prevalence of PAH and identify its independent risk factors among methamphetamine users.Methods and analysis The Screening Of Pulmonary Hypertension in Methamphetamine Abusers (SOPHMA) study will be a multicentre, cross-sectional screening study that will involve substance abuse clinics, hospitals and rehabilitation facilities in Hong Kong that cater to more than 20 methamphetamine users. A total of 400 patients who (1) are ≥18 years at enrolment; (2) report methamphetamine use in the last 2 years; (3) are diagnosed with methamphetamine use disorder; and (4) voluntarily agree to participate by providing written informed consent will be included. Patients will undergo standard echocardiography-based PAH screening procedures recommended for those with systemic sclerosis. Right heart catheterisation will be offered to participants with intermediate or high echocardiographic probability of PAH. For participants with a low echocardiographic probability of PAH, rescreening will be performed within 1 year. The primary measure will be the prevalence of PAH in methamphetamine users. The secondary measures will be the risk factors and a prediction model for PAH in methamphetamine users.Ethics and dissemination The SOPHMA study has been approved by the institutional review board. The findings of this study will provide the necessary evidence to establish universal guidelines for screening of PAH in methamphetamine users. Our results will be disseminated through immediate feedback to study participants, press release to the general public, as well as presentation in medical conferences and publications in peer-reviewed journals to healthcare providers and academia worldwide.